2023
DOI: 10.4102/phcfm.v15i1.3790
|View full text |Cite
|
Sign up to set email alerts
|

Practice, attitudes and views of right to access of sexual and reproductive health services by LGBTQI among primary health care nurses in Tshwane

Abstract: Background: Sexual and reproductive healthcare services (SRHS) are crucial investments for improving individual well-being and granting an opportunity to exercise sexual and reproductive rights. Primary health care (PHC) nurses are described as gatekeepers, preventing many individuals, including the members of the lesbian, gay, bisexual, transgender, queer and intersex (LGBTQI) community, from accessing much-needed healthcare services.Aim: The study aimed at exploring the experiences and perceptions of PHC nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, Seretlo and Mokgatle [14] found that some primary healthcare (PHC) nurses had a judgmental attitude and were surprised that there were queer patients, associating their sexuality with childhood traumas, whilst other PHC nurses were not judgmental and were willing to serve patients despite their sexuality. Additionally, a Tanzanian study found that certain HCPs actively helped to limiting access to healthcare for men of varied genders and sexualities [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Seretlo and Mokgatle [14] found that some primary healthcare (PHC) nurses had a judgmental attitude and were surprised that there were queer patients, associating their sexuality with childhood traumas, whilst other PHC nurses were not judgmental and were willing to serve patients despite their sexuality. Additionally, a Tanzanian study found that certain HCPs actively helped to limiting access to healthcare for men of varied genders and sexualities [29].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these SDGs, notably SDG 3.7, seek to provide universal access to sexual and reproductive healthcare services by 2030 [7]. Speci cally, in SA, queer people continue to face di cult and diverse social challenges such as prejudice, stigmatization, denial of healthcare services, and community rejection [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…23 Investments in sexual and reproductive healthcare are of utmost importance as they enhance the well-being of people and enable them to exercise their rights pertaining to sexual and reproductive matters. 24 Evidence shows that an increasing number of environmental contaminants are harming men's sperm quality, women's menstrual cycles and fertility potential. One contaminant may work via a number of distinct pathways, but these have yet to be completely defined in human studies, and further study is needed to discover the mechanisms through which contaminants exert their pathophysiological effects.…”
Section: Common Reproductive Issues In Men and Womenmentioning
confidence: 99%
“…However, some healthcare providers (HPCs) do not regard SRHSNs for genderqueer individuals as specific and unique [11], which means certain HCPs are unable to understand and respect genderqueer individuals' specific and unique healthcare needs fully, particularly regarding SRHSNs. According to some research, some HCPs' heteronormativity and cisnormativity approaches continue to be barriers to gender-fluid individuals accessing SRHSNs [12].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment guidelines are also considered heteronormative [13]. For example, HCPs continue to perceive and assume genderqueer individuals incorrectly as heterosexual [14,15], and HCPs regard most genderqueer individuals to be the same as any other patient [11], even though some gender-fluid individuals indeed have needs like gender transition, which includes gender-affirming surgeries and hormone therapy [16].…”
Section: Introductionmentioning
confidence: 99%